Optimisation of multi-petawatt laser-driven proton acceleration in the relativistic transparency regime - J Goodman; M King; R Wilson; R J Gray; P McKenna (New Journal of Physics, 2022)
Laser-driven proton acceleration from ultrathin foils in the relativistic transparency regime is investigated using 2D and 3D particle-in-cell simulations. The optimisation of the maximum proton energy and the overall laser-to-proton energy conversion efficiency with the onset of transparency is investigated for linearly and circularly polarised laser light at intensities up to 2 × 10 ^23 W cm ^−2 . The effects of the rising edge of the laser intensity profile and radiation reaction at the most extreme laser intensity are considered. It is found that the time at which transparency occurs relative to the peak of the laser pulse interacting with the plasma is a defining parameter in the optimisation of proton acceleration, over the full range of parameters explored.